The Role of Cowmilk’s Colostrum as the Source of Passive Immunity and Growth Factor for Improving the Haematological Status and Titre of Antibody against Hog Cholera in Pre-Weaning Piglets - Ida Bagus Komang Ardana (Journal of Global Pharma Technology, 2019)
Background: pre-weaning piglets often suffer from anemia, and infected with the bacteria so as growth slows even death. Aim: The purpose of this study was to determine the effect of cow colostrum administration on hematology profile and anti-body titers as an immunomodulatory effect to prevent germ infection. Methods: Seventy two piglets were divided in 4 groups in this research. Group who were not given bovine colostrum as a control, group who were given cow colostrum dose of 3 ml per animal, groups of piglet given bovine colostrum dose of 6 ml per animal, and a group of bovine colostrum piglet given a dose of 9 ml per animal. At the age of 7 days vaccinated against Hog Cholera and repeated at 14 days. Besides, at the period of 20 days all the piglets to have blood drawn and then accommodated in a vacuum tube which already contains anticoagulant (EDTA) for examination hematological profile is checked with Automated Manual VET ABC Blood Counter, made in Germany. Finally at the age of 30 days all piglet blood drawn and then accommodated in the tube for examination Hog Cholera antibody titer by ELISA. The data were analyzed with statistical test. Result: The results showed bovine colostrum supplementation at a dose of 1-5 days of age piglet 3-9 ml/piglet can raise the profile hematology and Hog cholera antibody titer. Conclusion: Addition of cowmilk’s colostrum in pre-weaning for the first five days of life could improve both the hematological profile and immunomodulatory set.Keywords: Piglet, Bovine colostrum, Hematology.